1997
DOI: 10.1007/s004030050206
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of vitamin D receptor levels by 1,25(OH) 2 vitamin D 3 in cultured human keratinocytes

Abstract: The natural biologically active form of vitamin D3, 1,25-dihydroxyvitamin D3 (1,25(OH)2D3), possesses antiproliferative, prodifferentiating and immunomodulatory properties. The actions of 1,25(OH)2D3 are mediated through the intracellular vitamin D receptor (VDR), and the level of VDR is believed to determine the cellular responsiveness to vitamin D3. In the present study we examined the effects of 1,25(OH)2D3 on the expression of VDR and its message in cultured human keratinocytes. Western analysis showed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 0 publications
5
13
0
Order By: Relevance
“…This observation is consistent with previous data reported in the literature, showing that mean intracellular VDR content is higher in undifferentiated than in differentiated cells [35, 38]. Moreover, VDR expression is sustained in myoblasts of different origins as well as in the developing skeletal muscle [21, 39, 40].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation is consistent with previous data reported in the literature, showing that mean intracellular VDR content is higher in undifferentiated than in differentiated cells [35, 38]. Moreover, VDR expression is sustained in myoblasts of different origins as well as in the developing skeletal muscle [21, 39, 40].…”
Section: Discussionsupporting
confidence: 92%
“…Of interest, in the AH130 hosts treated with VitD, muscle VDR levels were higher than those detected in the untreated tumor-bearing rats, likely in view of the restoration of normal circulating vitamin levels. In this regard, it is well known that VitD positively regulates the expression of its main receptor both in vivo and in vitro [34, 35]. The other way round, the present study shows that increased VDR levels in the muscle of tumor-bearing animals seems a constant finding, irrespective of changes in circulating VitD levels.…”
Section: Discussionsupporting
confidence: 74%
“…These results are in line with our recent data (Weber et al, 2005) and indicate that the upregulation of hCAP18 mRNA is associated with UVB-induced production of vitamin D. The upregulation of VDR after UVB irradiation is in accordance with previous findings demonstrating that vitamin D induces the expression of VDR in keratinocytes (Solvsten et al, 1997). The regulation of VDR expression, however, seems complex and it has been reported that UVB transiently downregulates the expression of VDR in keratinocytes in vitro up to 24 h following irradiation (Courtois et al, 1998 In humans, skin is the major source for vitamin D and interestingly its production in response to UVB is conserved through evolution.…”
Section: Uvb Upregulates the Antimicrobial Protein Hcap18 Mrna In Humsupporting
confidence: 94%
“…2A, 1,25-(OH) 2 D 3 up-regulated CCR10 expression in KAR PAS-620 cells. 1,25-(OH) 2 D 3 also up-regulated VDR expression, as reported previously (43). By real-time PCR, it was determined that 1,25-(OH) 2 D 3 up-regulated the levels of CCR10 mRNA and VDR mRNA in KARPAS-620 cells several folds (Fig.…”
Section: Identification Of the Major Regulatory Elements In The Humansupporting
confidence: 55%